Application of Discrete-Event Simulation in Health Care : A Preliminary Studies - Berlianty, Intan; Astanti, Yuli Dwi; Soejanto, Irwan (SENATIK STT Adisutjipto, 2019)
Simulation is one of the tools to solve the problems in a system, including hospital systems. The hospital has objectives and entities that are different from other systems, namely service to patients (humans) primarily, so making some decisions requires consideration due to the complexity of the variables within them. This preliminary study will discuss what problems might occur in the hospital and how the application of the simulation in solving the problem. Based on observations and interviews conducted, it is known that there are four issues: 1.) hospital services 2.) labor allocation (nurses) 3.) capacity and number of rooms/beds 4.) drug supply. Based on the literature search results, it is known that the simulation has the ability to solve these problems. The results of this literature review will then be used as a basis for developing simulation models in hospitals which are the object of research.